PENGARUH BUDAYA ORGANISASI, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN (Studi pada Sekretariat Daerah Kabupaten Rembang) - Eka Ruya Sulistyaningsih, 13.05.51.0017 (Students' Journal of Economic and Management, 2018)
ABSTRACT This study aims to determine the effect of organizational culture, motivation and work discipline on the performance of employees of the Regional Secretariat of Rembang Regency. The sampling technique of this study was Accidental Sampling which amounted 120 people. Collecting data uses questionnaires (questionnaires) by distributing a list of statements to respondents in order to obtain information. The research objective was formulated to determine the influence of organizational culture, motivation and work discipline on employee performance. Data collected using factor analysis to test the validity of item statements, the Crombach Alpha formula to test instrument reliability, regression analysis to examine the effect of partially each independent variable tested by regression analysis. The research results are: (1) Organizational Culture has a positive and significant influence on employee performance. (2) Motivation has a positive and significant influence on employee performance. (3) Work discipline has a positive and significant influence on employee performance. Keywords: Organizational Culture, Motivation, Work Discipline.